The Role of Dendritic Brain-Derived Neurotrophic Factor Transcripts on Altered Inhibitory Circuitry in Depression - Oh, Hyunjung; Piantadosi, Sean C.; Rocco, Brad R.; Lewis, David A.; Watkins, Simon C.; Sibille, Etienne (Biological psychiatry (1969), 2019)
A parallel downregulation of brain-derived neurotrophic factor (BDNF) and somatostatin (SST), a marker of inhibitory gamma-aminobutyric acid interneurons that target pyramidal cell dendrites, has been reported in several brain areas of subjects with major depressive disorder (MDD). Rodent genetic studies suggest that they are linked and that both contribute to the illness. However, the mechanism by which they contribute to the pathophysiology of the illness has remained elusive. With quantitative polymerase chain reaction, we determined the expression level of BDNF transcript variants and synaptic markers in the prefrontal cortex of patients with MDD and matched control subjects (n = 19/group) and of C57BL/6J mice exposed to chronic stress or control conditions (n = 12/group). We next suppressed Bdnf transcripts with long 3′ untranslated region (L-3′-UTR) using short hairpin RNA and investigated changes in cell morphology, gene expression, and behavior. L-3′-UTRs containing BDNF messenger RNAs, which migrate to distal dendrites of pyramidal neurons, are selectively reduced, and their expression was highly correlated with SST expression in the prefrontal cortex of subjects with MDD. A similar downregulation occurs in mice submitted to chronic stress. We next show that Bdnf L-3′-UTR knockdown is sufficient to induce 1) dendritic shrinkage in cortical neurons, 2) cell-specific MDD-like gene changes (including Sst downregulation), and 3) depressive- and anxiety-like behaviors. The translational validity of the Bdnf L-3′-UTR short hairpin RNA–treated mice was confirmed by significant cross-species correlation of changes in MDD-associated gene expression. These findings provide evidence for a novel MDD-related pathological mechanism linking local neurotrophic support, pyramidal cell structure, dendritic inhibition, and mood regulation.